Double seropositive neuromyelitis optica associated with COVID-19: A case report - Antonescu Ghelmez, Dana; Moraru, Adriana; Antonescu, Florian; Chelmambet, Altay Sercan; Bucur, Amanda Ioana; Tuţǎ, Sorin (Frontiers in Neurology, 2022)
Neuromyelitis optica spectrum disorders are characterized by severe demyelination and axonal damage with autoimmune mechanisms, predominantly targeting the optic nerves and the spinal cord. Patients often test positive for anti-AQP4 antibodies, while some have anti-MOG antibodies. Double seropositivity has been described, with a variable prevalence (0 to 26%) dependent on the testing method. The clinical significance of double seropositivity remains unclear. We present the case of a 65-year-old patient, admitted to our clinic with optical neuritis, followed up approximately 10 days later by cervical myelitis, who tested positive for both anti-AQP4 and anti-MOG antibodies. The clinical onset coincided with a mild form of SARS-CoV-2 infection. The neurological symptoms were initially relatively subdued, which delayed the diagnosis. The patient was not vaccinated against SARS-CoV-2. The clinical picture was compatible with an anti-AQP4 phenotype. The patient was started on corticosteroid therapy, under which the clinical response was good. Our case reinforces the idea that SARS-CoV-2 can precipitate autoimmune demyelinating diseases since SARS-CoV-2 infection has already been demonstrated as a risk factor for NMOSD relapses. To the best of our knowledge, this is the first reported case of double seropositive neuromyelitis optica associated with COVID-19. We expect that in the near future, as the true burden of COVID becomes clearer, we shall encounter other cases which can trace their apparent clinical onset to a SARS-CoV-2 infection. Careful attention should be paid to the apparent minor neurological symptoms of COVID-19.